Think Talk Write Assisted Monopoly Media in Students' Simple Essay Writing Skills - Iftitah, Nurlaili; Widiana, I Wayan; Simamora, Alexander Hamonangan (Universitas Pendidikan Ganesha, 2020)
Lack of student interest in writing essays, this happens because teachers in learning do not use innovative learning models, and learning media that interest students. Therefore, this study aims to analyze the use of Think Talk Write (TTW) learning models assisted by monopolistic media on simple essay writing skills of third-grade elementary school students. This type of research is quasi-experimental (quasi-experimental) with a non-equivalent post-test only control group design. The study population was all grade III in elementary school. The research sample was taken using a random sampling technique, with a total of 59 people. Data collection instruments used in this study were simple essay writing skills instruments, then analyzed using descriptive statistics and inferential statistics (t-test). Based on the results of the t-test analysis, the t-count was 11.457. While the table with db = 57 and a significance level of 5% is 2.002. This shows that t-count is greater than t-table (t-count> t-table) with the conclusion that the Think Talk Write (TTW) learning model assisted by monopoly media has a positive effect on writing skills in simple essays. The existence of this research helps teachers to enrich references to models and instructional media that can be used.